The Notary's Obligation to Read Deeds Between Fiqh al-Tawthiq and Positive Law: A Maqasid al-Shariah Analysis of Normative Ambiguity in Article 16 of the Indonesian Law on Notary Position - Johan Eko Cahyono; Tahegga Primananda Alfath; Khusnul Yakin (Universitas Ibn Khaldun, 2026)
The documentation of legal transactions occupies a distinctive place in Islamic law: Qur'an, Surah Al-Baqarah (2): 282, commands believers to record debts in writing through a just scribe (katib bi al-'adl), a command that classical fiqh literature on tawthiq (authentication) and shurut (legal formulae) developed into an elaborate doctrine of documentary certainty long before the emergence of the modern civil-law notariat. This study examines the Indonesian notary's statutory obligation to read authentic deeds under Article 16 of the Law on Notary Position (Law Number 2 of 2014) against this Islamic legal-documentary tradition, alongside the secular jurisprudential lenses of Hans Kelsen's hierarchy of norms and Gustav Radbruch's principle of legal certainty. Article 16 exhibits an internal disharmony: paragraph (1) letter (m) imposes a mandatory reading obligation reflecting the fiqh requirement that a just scribe ensure the parties' informed consent, paragraph (7) permits an exception based on the appearers' bare declaration, and paragraphs (8) and (9) retain sanctions, including degradation to a private deed, for procedural non-compliance. Using normative legal research combined with a maqasidi-usuli approach, this study treats the Qur'anic mudayanah verse and classical tawthiq literature as an Islamic primary source parallel to Indonesian positive legislation, and analyzes both through statutory, conceptual, and case approaches. The analysis shows that, viewed through usul al-fiqh, paragraph (7) functions as a nass mujmal (an ambiguous legislative text) that has never received the bayan tafsiri (explanatory clarification) needed to reconcile it with the sanction provisions in paragraphs (8) and (9) — a diagnosis that converges strikingly with Kelsen's finding of an unresolved validity conflict between a derivative exception-norm and its parent obligation. Because Indonesian notarial deeds are also the principal instrument for documenting Sharia-compliant contracts (akad syariah) such as murabahah, ijarah, and hibah, this disharmony carries direct consequences for the legal certainty of Islamic commercial and family-law transactions, not only for secular civil transactions. The study proposes a clause-referenced verification standard and an explicit burden-of-proof rule for Article 16 paragraph (7), justified simultaneously under maslahah mursalah and the positive-law objective of legal certainty. Keywords: Notary; fiqh al-tawthiq; Maqasid al-Shariah; hierarchy of norms; legal certainty; deed reading obligation.